Strategies for Structuring Musical Performances to Optimize Sidewalk Use in Kayutangan, Malang City - Jessica Shearen Wijaya Rudijanto; Lydia Graceanova Wahyudi; Lailla Dwi Yulitasari (Journal of Transformative Governance and Social Justice, 2025)
This study examines the regulatory strategy of music performances in increasing sidewalk usage in the Kayutangan area, Malang City. The Kayutangan area, in the heart of Malang City, is a regional area that has been revitalized to improve the region’s quality through developing the creative economy, especially in the arts and culture. Problems arise when sidewalks, which should be the right of pedestrians by law No. 20/2009 on road traffic and transportation, now double as a place of social interaction and a place for artistic expression. This study applies a qualitative approach based on a literature review by analyzing various related academic sources. The research findings indicate that the strategy for organizing music performances in Kayutangan requires a comprehensive approach that considers the distribution of sidewalk zones (frontage zone, pedestrian traffic zone, street furniture zone, and buffer zone), performance schedule arrangement, and SWOT analysis. The Malang City government, through Disporapar, has determined 4-5 performance locations with a fixed schedule every weekend. However, challenges remain, such as crowds blocking pedestrian traffic and unorganized street vendors. This study suggests the importance of cooperation between the government, the community, and local citizens to realize sustainable management. Optimizing the sidewalks for the musical performances in Kayutangan can positively impact the cultural, cultural, and economic aspects. However, it requires a structured arrangement that still pays attention to the primary function of the sidewalk as a pedestrian.